Ketepatan dan Kelengkapan Informasi Medis dalam Kaitannya dengan Keakuratan Kode Diagnosis - Maya Weka Santi; Ratna Umi Azizah; Feby Erawantini; Gamasiano Alfiansyah (FORIKES, 2022)
In the medical record, the diagnosis code is used as a reference in determining the cost of health services for patients. This study aims to determine the relationship between the accuracy and completeness of medical information with the accuracy of the diagnostic code. The method used was a literature review by analyzing 10 articles from various sources. There were 6 articles that discussed the relationship between the accuracy of medical information and the accuracy of the diagnosis code, with 5 articles showing that accuracy had a relationship with the factors of writing inappropriate medical terminology and not in accordance with the ICD-10, as well as writing an unclear diagnosis. Regarding the completeness of medical information, there were 4 articles that discussed the relationship between the completeness of medical information and the accuracy of the diagnosis code, with 3 articles that showed a relationship between the completeness of medical information and the incomplete and unclear writing factor of the patient's condition, as well as the lack of awareness of filling in the information. patient medical.Keywords: diagnosis code; medical information; accuracy; completenessABSTRAK Dalam rekam medis, kode diagnosis digunakan sebagai acuan dalam penentuan besarnya biaya pelayanan kesehatan bagi pasien. Studi ini bertujuan untuk mengetahui hubungan antara ketepatan dan kelengkapan informasi medis dengan keakuratan kode diagnois. Metode yang digunakan adalah literature review dengan menganalisis 10 artikel dari berbagai sumber. Didapatkan 6 artikel yang membahas tentang hubungan antara ketepatan informasi medis dengan keakuratan kode diagnosis, dengan 5 artikel menunjukkan bahwa ketepatan memiliki hubungan dengan faktor penulisan terminologi medis yang tidak tepat dan tidak sesuai dengan ICD-10, serta penulisan diagnosis yang tidak jelas. Tentang kelengkapan informasi medis, didapatkan 4 artikel yang membahas tentang hubungan antara kelengkapan informasi medis dengan keakuratan kode diagnosis, dengan 3 artikel yang menunjukkan adanya hubungan antara kelengkapan informasi medis dengan faktor penulisan kondisi pasien yang tidak lengkap dan tidak jelas, serta kurangnya kesadaran akan pengisian informasi medis pasien.Kata kunci: kode diagnosis; informasi medis; ketepatan; kelengkapan